Preservation of Mulyosari Site: An Initial Plan - Taniardi, Putri Novita; Utama, Bakti; Darojah, Citra Iqliyah; Nandiwardhana, Anggara (PURBAWIDYA, 2022)
This paper aims to explain the management plan of the Mulyosari site in accordance with the social and cultural potential of Banyuwangi. There are two methods of data collection, through literature studies and Focus Group Discussion (FGD). The study of literature comprises archaeological and historical data from the prehistoric to the historic era. It also comprises social and cultural data for the present-day Banyuwangi. Meanwhile, FGD comprises an overview of stakeholder perceptions of the Mulyosari site and the expected management plan. Based on that, the Mulyosari site shortterm management plan was compiled. The management plan is still open to any adjustments in the future. It has adaptive sense in line with the ongoing archaeological research at the Mulyosari site. There are two actions that need to be taken immediately: first, conducting comprehensive archaeological research, and second, official stipulating the Mulyosari site as a cultural heritage site. Such actions are considered an initial plan for the management of the cultural site. It adheres to the principle of preservation as stated in UU Cagar Budaya No 11 Tahun 2010.